Hazarat Sulaiman (AS) - Karam , Ambia (Lahore , Karachi Children's publication)
He was known for his great wisdom and wealth, as well as his ability to communicate with animals and control the jinn (spirits). At a young age, Sulaiman was chosen by Allah to be a prophet and ruler. He succeeded his father as king at the age of 12 and immediately began to strengthen his kingdom